Production Line Efficiency Management in the Context of Product Portfolio Expansion : Case study - Strömberg, Joona (My University, 2026)
The topic for this thesis is the production line efficiency management in the context of product portfolio expansion. The case company is working in the field of paper industry and the produc-tion line is facing challenges regarding the expanding product portfolio. The main aim for the thesis is to find ways to keep the efficiency level of the production line in a level that it has been before the expansion of product portfolio, or possibly improve it. The project is completed in a four person project team, which consists of project manager, sup-ply chain planner, supervisor and production engineer. The team has been carefully selected in a mindset that there would be as much expertise as possible around the theme of the study. Other people from the organization are being contacted in the project as well for consultancy, and to increase the knowledge of certain project phases. The research method for the study is quantitative and the solutions for the thesis will be created with the help of constructive method. Sample size for the study is around 200 000 measure-ments. The data used in the case study has been collected from the case company on a monthly basis to measure the progress of the project. The project has been done with a selected frame-work of stakeholder management and DMAIC. DMAIC and stakeholder management have been selected as the framework because the project affects multiple stakeholders and Lean Six Sigma is a mindset that the factory works around. The case study focuses around three different controllable topics: reference cycle, unplanned stock and grade change waste. The topics are measured with eight different key performance indicators that are updated regularly to track the progress of the project. All of the enhancement ideas for the three topics are being evaluated and analyzed before implementing them into the production line and the results of the implementations are being measured monthly to avoid any possible challenges or mistakes that would be caused by the improvements. The results of the project shows that by enhancing the reference cycle, the production line effi-ciency increases in almost every key performance indicator. By increasing the volume of the production runs, the waste reduces and the production line becomes more efficient and leaner. One of the outcome from the project was a tolerance amendment to paper grade change and it is a suggestion to the case company to test and implement the idea to the production line as they best see. Other suggestions of the study are targeted to unplanned stock to improve the management and material flow of the stock.

Diplomityön aihe on tuotantolinjan tehokkuuden hallitseminen tuoteportfolion kasvaessa. Yritys X toimii paperiteollisuudessa ja yhdellä tuotantolinjalla on haasteita kasvavan tuoteportfolion vaikutuksista tuotannon tehokkuuteen. Diplomityön tarkoituksena on löytää tapoja pitää tuotannon tehokkuus aikaisemmalla tasolla tai jopa parantaa tuotannon tehokkuutta. Projekti tehdään neljän hengen projektitiimillä, johon kuuluu projektipäällikkö, tuotannonsuunnittelija, tuotannon esimies sekä käyttöinsinööri. Projektitiimi on valittu siten, että projektitiimillä olisi mahdollisimman paljon asiantuntemusta projektiin liittyviin aiheisiin. Organisaation muita henkilöitä konsultoidaan myös projektin aikana, jotta saataisiin mahdollisimman kattavaa tietoa projektin onnistumisen takaamiseksi. Tutkimusmenetelmänä diplomityössä käytetään kvantitatiivista tutkimusta ja tutkimustulokset analysoidaan konstruktiivisella menetelmällä. Mittausten määrä tutkimuksella on noin 200 000 tulosta. Diplomityössä käytettyä dataa on kerätty Yritys X:ltä kuukausittain, jotta pystytään seuraamaan projektin kehitystä. Diplomityön raameina käytetään sidosryhmäjohtamista ja DMAIC:ia. DMAIC ja sidosryhmäjohtaminen on valittu raameiksi, koska projekti vaikuttaa moniin sidosryhmiin ja tehdas noudattaa Lean Six Sigman periaatteita. Diplomityö keskittyy kolmeen hallittavaan aiheeseen: ajosykliin, lattiavarastoon ja lajinvaihtohylkyyn. Aiheita seurataan kahdeksan eri keskeisen suorituskykymittarin avulla, joita päivitetään säännöllisesti projektin seuraamisen mahdollistamiseksi. Kaikki kehitysideat kolmen hallittavan aiheen parantamiseksi arvioidaan ja analysoidaan ennen niiden implementointia tuotantolinjaan. Implementointien tulokset mitataan ja arvioidaan kuukausittain, jotta vältytään mahdollisilta haasteilta ja ongelmilta, joita implementoinneista voisi syntyä. Projektin tulokset osoittavat, että parantamalla ajosykliä saadaan lisättyä tuotantolinjan tehok-kuutta lähes jokaisen suorituskykymittauksen mukaan. Lisäämällä tuotantoajojen kokoa, hylyn määrä laskee ja tuotantolinjasta tulee tehokkaampi sekä hukka vähenee. Yksi projektin seurauksista on toleranssien muutos lajinvaihdoissa. Tämän kehityksen jatkaminen on jatkosuositus yritykselle ja heidän kannattaisi testata sekä implementoida idea tuotantolinjalle heidän parhaan näkemyksensä pohjalta. Muita suosituksia diplomityössä ovat lattiavaraston hallinnoimisen ke-hittäminen sekä sen materiaalivirran parantaminen.
Keywords: Strategic Project Management; Master’s Programme in Industrial Engineering and Management